STRUCTURAL ANALYSIS ON NANOCOMPOSITES LEAD FREE SOLDER USING NANOINDENTATION - Bachok, Z.; Saad, A.A.; Abas, M.A.; Ali, M.Y.T.; Fakpan, K. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
As lead-based solder has been restricted, the microelectronics industry has been looking for lead-free solder like SAC. But there have been cases of solder joints failing, reducing product reliability because the formed intermetallic compound layer (IMC) is brittle. The thick IMC layer reduced the solder joint strength. This paper analyses real industrial package assemblies of nanocomposite lead-free solder joints. TiO2, Fe2O3, and NiO nanoparticles with 0.05 weight percentage (wt.%) were mixed into 96.5% Sn-3.0% Ag-0.5% Cu (SAC305) solder paste using a mechanical stirrer to make nanocomposite lead-free solders. The effects of nanoparticles in miniaturized solder on joining quality in IMC layers and nanocomposite solders were studied using a scanning electron microscope (SEM) and a nanoindenter. Adding TiO2, Fe2O3, and NiO nanoparticles changed the microstructure and reduced the IMC layer thickness by 29%-35%. The nanocomposite solder’s hardness and elastic modulus are increased by 1%-11% and 8%-31%, respectively. In comparison to pure SAC305, the composition of SAC305 with NiO nanoparticles solder paste had the highest hardness, and with Fe2O3 had the highest elastic modulus. This proves that the incorporation of nanoparticles of TiO2, Fe2O3, and NiO has enhanced the mechanical properties of pure SAC and increased the reliability of solder joints in miniaturised electronic packaging.